THE INFLUENCE OF SOCIAL MEDIA MUKBANG CONTENTS TOWARDS ADOLESCENT FOOD CONSUMPTION BEHAVIOR - Olova, Khansa Ranbia Audreyzovna; Windah, Andi; Riza, Ahmad; Nurhaida, Ida (Universitas Sang Bumi Ruwa Jurai, 2024)
How individuals eat has an impact on their health and well-being. To maintain their well-being, individuals must control their mindset and social environment. The prevalence of eating broadcasts on YouTube, where content creators consume large amounts of food without revealing nutritional information, continues to be a popular trend that hypothetically affects people's eating habits. The study aims to assess the influence of social media influencers on unhealthy food habits, using Planned Behavior Theory as a framework. This study used a method of survey and collecting quantitative data. This study examined the research site of the University of Lampung. The data analysis was done descriptively. According to the regression formula, Y = 16. 615 + 0677X - Constant term = 16. In summary, with a trust value of 0, 615 indicates a positively oriented regression coefficient X, which represents the magnitude of influence of the X variable on the Y variable. The t-test showed X had a significant impact of 40. 1% on Y 59 remaining. 9% of variation in the Y variable attributed to unexamined factors. The study showed that how much a person's food consumption behavior is affected by watching an eating broadcast depends on their intentions. Consuming the frequency, duration, and attention levels of the broadcast significantly affects and improves unhealthy consumption behavior in adolescents.